Purificação de extrato de pequi (Caryocar brasiliense Camb.) utilizando coagulantes naturais e processo de filtração por membranas - Magalhães, Flávia de Santana (2018)
Nowadays, the interest on extracting bioactive compounds derived from plants, especially polyphenols, has been growing. Moreover, the interest on studing unconventional fruits, such as pequi (Caryocar brasiliense Camb.), which is a native Brazilian cerrado fruit that contains large amounts of total phenolic compounds in its pulp, has also been growing. Recovery of the phenolic compounds is often carried out through extraction and concentration processes. These processes are conventionally done by heating, that causes degradation of some bioactive compounds. Thus, the membrane separation process, in which there is no application of temperature, is a viable alternative to avoid this type of degradation. This study aimed to chose the best conditions for the aqueous extraction of phenolic compounds from pequi pulp, to clarify the extract using chitosan and moringa seeds (Moringa oleifera) and to concentrate the phenolic compounds using membrane separation process. Extraction of the bioactive compounds was performed at 80 °C at a solution concentration of 25 g of pulp in 100 mL of water. After extraction, different bioadsorbents (chitosan and whole and defatted moringa seeds) were evaluated for the clarification of pequi extract. The appropriate concentrations of these adsorbents (chitosan 0.1 g/L (EQ) and moringa 2 g/L (EM)) were then determined for clarification. Compared with the only centrifuged extract (EC), the EQ increased permeate flux in the microfiltration process by approximately 35% using a membrane with pores of 0,22 μm. Microfiltration was able to reduce the total solids content in 56, 56, and 50% and lipids in 72, 67 and 45% compared to EC, EM and EQ extracts, respectively. Microfiltration permeate was then ultrafiltered and, in turn, this sequential process caused reduction of 50 and 90% of the lipid content and 21 and 23% of the total solids to EM and EQ, respectively, and was able to retain 43 and 42% of phenolic compounds present in the microfiltered extracts of moringa and chitosan, respectively. Sequential nanofiltration of the ultrafiltration permeate was able to retain 54% of the total solids content but there were only 31% retained phenolic compounds. The direct ultrafiltration of the EC and EQ extracts was able to retain 65% of the phenolic compounds and reduced the values of total soluble solids (56 and 45% for EC and EQ, respectively), total solids (78% and 74% for EC and EQ, respectively) and lipids (approximately 98% for the two extracts). Direct nanofiltration completely reduced lipid content, retained 91% of phenolic compounds and reduced 82% in total solids content. However, as the permeate flux values were relatively low (1.24 L/h m²), direct ultrafiltration is suggested for the concentration of these compounds because it reduced the time process with respect to direct nanofiltration in approximately 3 h, ending the filtration with a permeate flux of 4.84 L/h m², 74% higher than the flux obtained in direct nanofiltration. .